THE PROSPECTS OF TURKISH RISE IN AFRICA AS A KEY PLAYER - V. A. Avatkov; Y. O. Tomilova (Vestnik MGIMO-Universiteta)
In article the analysis of foreign policy of Turkey during 2002-2012 in Africa is given. The special attention is paid to use of "the soft force" as main instrument of strengthening of influence of Turkey on the African continent. Problems and prospects of formation of Turkey as the leading player in Africa are considered. The integrated approach to cooperation is effective way of consolidation of positions of Turkey in Africa. In addition, that fact has impact on strengthening of influence of Turkey in Tropical Africa that the countries of this region never were under sovereignty of Turkey, so have no joint negative historical experience. Moreover, large volumes of humanitarian assistance and lack of any pressure from Turkey allow the African countries to feel grateful to the partner, but not restrained or obliged to it. Such approach allows to create favorable climate in the bilateral and multilateral relations and to strengthen trust.